Bridging the Divide? (American Journal of Islam and Society, 2006)
On January 9, 2006, in Washington, DC, the Saban Center for Middle EastPolicy at the Brookings Institution hosted the highest level meeting betweenthe Bush administration and the American Muslim community. Entitled “Bridging the Divide?” and organized by the Brookings Project on USPolicy toward the Islamic World, representatives of various Muslim organizationwere granted the opportunity to interface with C. David Welch, theAssistant Secretary of the Bureau of Near Eastern Affairs. The conference,a follow-up to previous initiatives on “Bridging the Divide” theme, soughtto bring together key leaders and specialists “to explore the potential spacefor the American Muslim community to assist and advance US policytowards the Islamic world and capabilities within the community that mightbe better tapped.” In attendance were representatives from the Americangovernment, officials from a variety of American Muslim organizations,American Muslim foreign policy experts, others from the Washington thinktankand policy communities, and students.In the opening speech, Welch acknowledged several unique characteristicsabout the American Muslim community: its integration into Americancivic life; being Americans as well as Muslims; and, despite post-9/11 tensions,steering a moderate course while confronting extremist Islamist tendencies.As evidence, he cited the Fiqh Council of North America’s recentfatwa against Islamic terrorism that was endorsed by major Muslim organizations.He recognized that American Muslims can play an exceptional rolein explaining the American position, given their cultural, linguistic, and ethnicties with the Islamic world, and acknowledged the history of conflictbetween the United States and the Muslim world. In addition, he condemnedthe seeming “civilizational strife” between Islam and the West as a pointless“jihad/crusade.” He stated that he was more comfortable with the relationshipof the United States with the Muslim – especially Arab – world as beingdefined by a dialog stressing the commonalities of belief in God, virtue,family life, and socioeconomic justice ...